A cross sectional study to assess the sFlt-1:PlGF ratio in pregnant women with and without preeclampsia - Vivek Pant; Binod Kumar Yadav; Jyoti Sharma (BMC, 2019)
Abstract Background Preeclampsia is a multisystem disorder characterized by vascular endothelial malfunction occurring after 20 weeks of gestation. Placental soluble fms-like tyrosine kinase-1 (sFlt-1) is an antiangiogenic factor and placental growth factor (PlGF) is a potent angiogenic factor. The imbalance between these factors during placenta and fetal development has been shown to play a role in endothelial damage in preeclampsia. Preeclampsia is the leading cause of maternal mortality in Nepal. This study was designed to compare the sFlt1:PLGF ratio in pregnant women with and without preeclampsia attending Tribhuvan University Teaching Hospital (TUTH). Method An observational cross-sectional study was performed in the Gynecology and Obstetrics Department of TUTH involving forty-four subjects with preeclampsia and forty-four age- and gestational-week-matched normal pregnant subjects as controls. Blood pressure, urinary protein levels, serum sFlt-1 levels, serum PlGF levels and the sFlt-1:PlGF ratio was compared in both the cases and control. The concentrations of sFlt-1 and PlGF were measured with commercially available ELISA kits. SPSS ver. 20.0 was used to analyze the data. Results There was no significant difference in age or gestational age in either study group. The ratio of the sFlt-1 and PlGF concentrations was significantly higher in women with preeclampsia (31.6 ± 9.6) than in the controls (3.2 ± 1.3). Likewise, diastolic blood pressure was significantly associated (p-value 0.000), whereas the severity of proteinuria was not associated (p-value 0.773) with the sFlt-1:PlGF ratio in women with preeclampsia. The significantly higher ratio (35.51 ± 8.1 versus 25.4 ± 8.7) was found in women with preeclampsia who developed complications than the group of women with preeclampsia who did not develop complication. Conclusion The sFlt-1:PlGF ratio is significantly higher in Nepalese women with preeclampsia than in normal controls and this finding can be applied for further planned clinical trials.